A Health inequalities in non-communicable disease mortality among Adult’s in Uganda : Health inequalities - Tumuhaise, Alex (Student’s Journal of Health Research Africa, 2025)
ABSTRACT Non-communicable diseases (NCDs), including cardiovascular diseases, cancers, chronic respiratory diseases, and diabetes, are leading causes of death worldwide, particularly affecting low- and middle-income countries (LMICs). This study systematically reviews the extent of health inequalities in NCDs mortality among adults across various demographic groups in Uganda. Methodology Assessment of key risk factors for NCDs using population data drawn from 3987 participants in a nationally representative baseline survey in Uganda was made. Five key risk factors considered for the indicator variable included: high frequency of tobacco use, low physical activity levels, high body mass index and raised blood pressure. A statistical modeling framework was developed and a multi nominal logistic regression model was fitted. The endogenous and exogenous predictors of NCDs were assessed Results A total of 1,210 deaths among persons ≥ 30 years old were reported from 2010 to 2016 (50.7% among women). Approximately 53% of all deaths were due to non-communicable diseases, 31.8% due to communicable diseases, 8.2% due to injuries, and 7% due to maternal-related deaths or undetermined causes. Cardiovascular diseases accounted for the largest proportion of NCD deaths in each year, and women had substantially higher cardiovascular disease mortality rates compared to men. Also, the review highlights significant disparities in NCD prevalence across different demographic groups in Uganda. Notably, the elderly population in rural areas shows a high prevalence of NCDs. Individuals living with HIV (PL-HIV) exhibit compounded health burdens, with hypertension being a common comorbidity. Urban-rural disparities in NCD prevalence is evident, with lifestyle factors associated with urbanization contributing to increased risks. Alarmingly, mortality rates attributable to NCDs, particularly cardiovascular diseases and diabetes, have risen over the past decade. Barriers to healthcare access, including geographic, financial, and policy-related challenges, exacerbate these disparities.